2022
DOI: 10.1177/09727531221108849
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intestinal Permeability Biomarkers in Schizophrenia: A Possible Link with Subclinical Inflammation

Abstract: Background and Purpose Emerging studies have shown that gut-derived endotoxins might play a role in intestinal and systemic inflammation. Although the significance of intestinal permeability in modulating the pathogenesis of Schizophrenia (SCZ) is recognized, not much data on the specific role of intestinal permeability biomarkers, viz., zonulin, lipopolysaccharide-binding protein (LBP), and intestinal alkaline phosphatase (IAP) in SCZ is available. Therefore, we measured the plasma levels of zonulin, LBP, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Zonulin is a known physiological modulator of intercellular tight junctions synthesized within intestinal and liver cells [ 17 ] that modulates the permeability of tight junctions between cells of the wall of the digestive tract. Zonulin has been used as an IP biomarker for autoimmune diseases such as inflammatory bowel disease (Crohn’s disease [ 31 ]), as well as multiple sclerosis [ 32 ] and Schizophrenia [ 33 ]. In the present study, the plasma level of Zonulin was significantly increased at 1 h and 16 h post blast exposure, indicating that blast may contribute to the impairment of the gut barrier in the paracellular pathway ( Figure 3 and Table 2 ), which was further supported by elevated bacteria alpha diversity in the blood transcriptome ( Figure 2 b and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonulin is a known physiological modulator of intercellular tight junctions synthesized within intestinal and liver cells [ 17 ] that modulates the permeability of tight junctions between cells of the wall of the digestive tract. Zonulin has been used as an IP biomarker for autoimmune diseases such as inflammatory bowel disease (Crohn’s disease [ 31 ]), as well as multiple sclerosis [ 32 ] and Schizophrenia [ 33 ]. In the present study, the plasma level of Zonulin was significantly increased at 1 h and 16 h post blast exposure, indicating that blast may contribute to the impairment of the gut barrier in the paracellular pathway ( Figure 3 and Table 2 ), which was further supported by elevated bacteria alpha diversity in the blood transcriptome ( Figure 2 b and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zonulin is a known physiological modulator of intercellular tight junctions synthesized within intestinal and liver cells [17] that modulates the permeability of tight junctions between cells of the wall of the digestive tract. Zonulin has been used as an IP biomarker for autoimmune diseases such as inflammatory bowel disease (Crohn's disease [31]), as well as multiple sclerosis [32] and Schizophrenia [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current immune findings in delirium partly overlap with previous findings in schizophrenia. Thus, in schizophrenia, several studies reported significant associations with increased bacterial translocation ( 78 80 ), breakdown of transcellular and paracellular tight/adherens junction barriers ( 23 , 81 , 82 ), as well as the BBB ( 24 , 83 ). Moreover, our study demonstrated a significant association between increased levels of IgA in P. gingivalis , H. pylori , and CDT (and their z composite score) and delirium severity.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study on the subject, plasma levels of both LBP and zonulin are significantly increased, and plasma intestinal alkaline phosphatase levels are found decreased among patients with schizophrenia. The authors suggest that metabolic endotoxemia-induced low-grade inflammation might play a role in the etiology of schizophrenia (Gokulakrishnan et al, 2022). For ASD, intestinal and blood-brain barrier (BBB) dysfunction because of permeability changes has gained interest, too.…”
Section: Discussionmentioning
confidence: 99%